Bahasa Inggris - Nurlela, Heni; Handayani, Tuty (UIN Alauddin Makassar, 2024)
This research examines the assertive acts employed by Joe Biden during his first interview as President on the 60 Minutes YouTube Channel. Using Searle & Vanderveken’s theory of speech acts, the study adopts a qualitative descriptive approach. Data collection involved watching videos, reading the transcript, and note-taking. The analysis identified 20 utterances which are categorized into eight types of assertive acts: admit, assure, claim, criticize, inform, rebut, report, and predict. The most frequently used of assertive act was “inform”, with 7 utterances, followed by